Cote d’Ivoire Climate-Smart Agriculture Investment Plan - World Bank Group (World Bank, Washington, DC, 2019)
Climate change threatens to bring substantial impacts to Côte d’Ivoire’s agriculture sector, which is central to the country’s economic productivity and food security. Climate change, of course, poses challenges not only for Côte d’Ivoire but also for countries across Africa. Côte d’Ivoire is a signatory to the United National Nations Framework Convention on Climate Change (UNFCCC) Paris agreement and has submitted its nationally determined contributions (NDC), committing to take action both on adaptation to climate change and on reducing greenhouse emissions. Côte d’Ivoire is by far a minor emitter of greenhouse gases. This document provides an investment plan for climate-smart agriculture (CSA) in Côte d’Ivoire, developed with support of the AAA Initiative and the World Bank, and technical assistance of the CGIAR Research Program on Climate Change Agriculture and Food Security (CCAFS). This plan includes a set of twelve key CSA investments for Côte d’Ivoire that were developed with strong stakeholder engagement, expert input and scientific evidence. Because it is a member of the AAA Initiative and is also committed to delivering on its NDC commitments, Côte d’Ivoire now has an investment plan that includes a set of specific climate-smart projects that improve productivity, build resilience to climate change and, as appropriate, reduce greenhouse gas emissions in the agriculture sector.